KARST ROLE IN THE FORMATION OF DIAMOND PLACERS OF THE MUNO-MARKHINSKII INTERFLUVE (YAKUTSK DIAMOND-BEARING PROVINCE, RUSSIA) - Afanas'ev V.P.; Zinchuk N.N.; Pokhilenko N.P.; Krivonos V.F.; Yanygin Yu.T. (My University, 2001)
The paper is devoted to the karst role in the formation of aureoles of kimberlite indicator minerals (KIM) and diamond placers in the modern alluvium of the Muna-Markha interfluve. Its territory is open, i.e., the Lower Paleozoic rocks hosting kimberlites and kimberlites themselves are exposed on the surface. Widely developed karst depressions are demonstrated to be the main suppliers of KIM and diamonds to the watercourse alluvium. These karst depressions were filled with Jurassic sedimentary material with KIM concentrations, which was mixed with authigenic iron minerals, i.e., limonite, magnetite, and hematite. This interpretation explains the high contrast in KIM distribution; i.e., sites with extremely high KIM concentrations alternate with watercourse areas devoid of heavy minerals. The revealed role of karst in KIM aureole formation in the open areas required an alteration of the panning sampling scheme, which was significantly improved. The kimberlite bodies of the Nakyn field located under the Jurassic sedimentary cover to the east from the Muna-Markha area, are accompanied by karst depressions. Some karst depressions in the open areas may also be associated with kimberlites. Therefore, the detailed study of karst and the comprehensive interpretation of magnetic anomalies are necessary for the discovery of kimberlite bodies. Most of these anomalies are produced by karst structures.
Keywords: Paleozoic; Jurassic; Палеозой; Mesozoic::Jurassic; Paleozoic; Мезозой::Юрская